Performance-Based Budgeting : Beyond Rhetoric - Moynihan, Donald P. (World Bank, Washington, DC, 2012)
Performance-based budgeting has long been a recommended reform in both industrial and developing countries. Yet considerable ambiguity remains on how to define and implement this approach. A relatively strict definition is that performance-based budgeting allocates resources based on the achievement of specific, measurable outcomes (Fielding Smith 1999). This definition promises a rational, mechanistic link between performance measures and resource allocations, with the ability to state the level of outputs that can be achieved with an additional amount of resources. But outputs cannot always be quantified precisely-and while performance information offers benefits to governments, it cannot eliminate the inherently political nature of budgeting. Over the past decade U.S. state governments have experimented extensively with performance- based budgeting. Yet while 47 of 50 states claim to use some form of it, driven by legislative or administrative requirements, there is no evidence that any state relies on a strict performance-based system. Even though U.S. state governments have fairly high human and financial capacity, they have encountered limitations in implementing performance-based budgeting-raising questions about the potential benefits of this approach.